Educational Cooperation Development Plan at SMAN 1 Sitiung, Dhamasraya Regency - Oktawira, Leni; Apriyenti, Apriyenti; Asmendri, Asmendri; Sari, Milya; Limei, Sun (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Cooperation in the field of education is a form of multi-level cooperation between various parties involved in the world of education, including government, educational institutions, industry, and society. The main objective of this cooperation is to improve the quality and relevance of education throughout the region. The results of this study are the development plan for cooperation between schools and related agencies in Dharmasraya including: (1) Health: Sitiung Health Center through UKS to improve student health (2) Public Services: Dharmasraya Police through the